New test methods to determine water absorption by capillarity. Experimental study in masonry mortars. (14th February 2022) - Yedra, Engerst; Ferrández, Daniel; Morón, Carlos; Saiz, Pablo
Highlights: Capacitive and resistive sensors present an efficient solution to determine capillary absorption. Mortars made with recycled aggregate absorb a higher amount of water by capillarity. Water by capillarity reaches higher levels in mortars made with natural aggregate. The sensors developed in this work reliably collect water absorption by capillarity. With the results, a statistical model has been developed for the response variable "absorption by capillarity". Abstract: In this work, two alternative methods are presented to evaluate the absorption of water by capillarity in masonry mortars. For this, two different types of sensors of our design have been developed, one capacitive and the other resistive. The measuring equipment has been tested in mortar samples made with three kinds of aggregates: natural, recycled ceramic, and recycled concrete. The results obtained employing the capacitive sensor show how there is a good correlation between the mass of water absorbed by the mortars and the variation in capacitance, taking into account that mortars made with recycled ceramic aggregate were the ones that present a higher capillary absorption coefficient and lower mechanical resistance. On the other hand, with the help of the resistive sensor, it has been possible to monitor in real-time the rise of water by capillarity inside the samples, determining how the percentage of humidity measured at different heights of the samples evolves. As a result, it has been observed that water experiences a greater rise due to capillarity in mortars made with natural aggregate.